Ethnogenesis: A Contested Model of Early Medieval Europe - Gillett, Andrew ca. 20./21. Jh. (History compass, 2006)
Recent research in late antique and early medieval history has paid much attention to ‘Ethnogenesis’. The historical model associated with this term explains the change from the classical world to medieval conditions as the effect of ethnic identification supplanting Hellenistic forms of public discourse. Culturally specific dynamics of ethnicity, arising from proto-historical northern Europe, are seen as the engines of change. Recent critiques of the approach, however, see both its methodology and historiographic assumptions as problematic. This article seeks to clarify the current debate, to set out the questions of evidence and interpretation for interested Medievalists, and to draw the attention of non-Medievalists to this historiographic debate over interpretative models for one of the major revolutions in western history. History Compass’ first PODCAST is now available The podcast is a discussion between Professor Felice Lifshitz, History Compass’ medieval Europe editor, and Dr Andrew Gillett, a published History Compass author. They examine Dr Gillet's published essay, ‘Ethnogenesis: A Contested Model of Early Medieval Europe’ and ask: What is ethnogenesis? What are the questions of evidence and interpretation for interested Medievalists? How do we draw the attention of non-Medievalists to the historiographic debate over interpretative models for one of the major revolutions in western history? Click here to launch the podcast: http://wiley.cdn.palmerhargreaves.com/podcast/hic3/hic3-01.mp3 (mp3 file, 14.4 MB, 20 minutes 33 seconds).